Effect of El-Niño Southern Oscillation (ENSO) on Heat Transport in The Indonesia Throughflow Passages and Ocean Heat Content in The Banda Sea - Pratama, Khafid Rizki; Radjawane, Ivonne Milichristi; Pratama, Bayu Edo (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2025)
Indonesia Throughflow (ITF) flows water mass from the Northern Pacific Ocean to the Indian Ocean through Indonesian waters. This research was conducted in the Eastern Indonesia waters in 2009–2019 using Copernicus Marine Environment Monitoring Service (CMEMS) reanalysis and World Ocean Database (WOD) to analyze heat transport in ITF passages and ocean heat content in the Banda Sea. The analysis shows that ITF and heat transport have a strong relationship with a correlation of 0.7 during El-Niño Southern Oscillation (ENSO). Regarding the vertical profile by depth, heat transport in the Makassar Strait during La Niña was detected to be stronger in the Labani Channel and Central Sulawesi water, with values of -1.2 PW and -0.6 PW. Then, in the Lifamatola Strait, it was identified as strengthening in the Lifamatola Channel and Halmahera Strait with a value of -0.5 PW and -0.3 PW. The lag correlation between heat transport and the Oceanic Niño Index (ONI) shows a lag time of around 3-4 months, with the ENSO preceding heat transport. Mixed layer depth has an inverse relationship and salinity has a direct relationship with ENSO. Meanwhile, salinity has a relationship that is directly proportional to the ENSO. Another influence is the Rossby (Kelvin) waves when La Niña (El Niño) propagates to the West (Central) Pacific region, which tends to cause higher (lower) sea level elevations so that ITF and heat transport become strong (weak). It causes the ocean heat content (OHC) to increase during La Niña and decrease during El Niño.